New Bio-surfactant used in the Synthesis of Functionalized Nanoferrites as Potential Catalysts - Virlan, Constantin; Florin Caltun, Ovidiu; Lutic, Doina; Pui, Aurel (Current Nanoscience, 2017)
Background: Organic dyes represented a serious pollutant in the past decades but does not present significant risk at the moment but still represents a model pollutant for the assessment of catalytic and photocatalytic activity of ferrite nanoparticles and more due to their ease in measurement. Methods: Ferrite nanoparticles were obtained using the co-precipitation method and Palm Oil as biosurfactant. The nanoparticles were fully characterized using the relevant methods. Their catalytic activity was evaluated for the degradation of commonly used dyes. Results: The nanoparticles present large magnetic moment and large specific surface suitable for environmental applications providing large adsorption surface and can be easily separated using an external magnetic field. The catalytic efficiency normalized to surface was maximum for copper ferrite. Conclusion: Food grade palm oil can be used to reduce the synthesis cost of pure ferrite nanoparticles usable as catalyst in the degradation of organic pollutants as tested using model dyes.
Keywords: surfactant synthesis